Risk factors associated with cystic echinococcosis in humans in selected pastoral and agro-pastoral areas of Uganda - Othieno, Emmanuel; Okwi, Andrew Livex; Mupere, Ezekiel; Zeyhle, Eberhard; Oba, Peter; Chamai, Martin; Omadang, Leonard; Olaki Inangolet, Francis; Siefert, Ludwing; Ejobi, Francis; Ocaido, Michael (Int J One Health, 2017)
It was to determine the risk factors responsible of occurrence of cystic echinococcosis (CE) of humans in the pastoral and agro-pastoral (PAP) in Uganda. Materials and Methods: A cross-sectional study was conducted in districts: Moroto, Napak, Nakapiripirit and Amudat in Karamoja region; in agro-pastoral communities of Teso region, in the districts of Kumi and Bukedea; Nakasongola district in Central region and in Kasese district in the Western region. People were subjected to voluntary ultrasound screening for CE. Those found positive to CE on ultrasound screening were interviewed using a special designed form to find out the probable predisposing factors for acquisition of CE infection. Predisposing factors considered were location, age, sex, dog ownership, occupation, water source, and religion. Univariate and multivariate logistic regression analysis was performed to identify key risk factors. Results: In Karamoja region, being female, age beyond 40 years and open spring water sources were the risk factors. While for Nakasongola age beyond 40 years was a risk factor. In Kasese dog ownership, age >60 years and being a Muslim were risk factors. In Teso region dog ownership and age >60 years were the risk factors. Conclusion: Being a pastoralist, a female, increasing age beyond 40 years, open spring water sources, dog ownership and being a Muslim were the risk factors for CE in PAP areas in Uganda.
Keywords: Agro-pastoral; Cystic echinococcosis; Humans; Risk factors pastoral; Uganda